Explaining a Decade of Inconsistency: A Systematic Review of AIS Effectiveness in Indonesia - Suci Ramadhanti Ahad; Agus Munandar (Journal of Social Research, 2025)
This study addresses the persistent inconsistencies in the literature regarding the effectiveness of Accounting Information Systems (AIS) in Indonesia. Employing a Systematic Literature Review (SLR) of 70 Sinta-indexed articles from 2014-2024, we find that while human resource competence and internal control systems are the most studied determinants of financial reporting quality, their reported impacts are highly contradictory. Our analysis reveals these inconsistencies are not random but are systematically driven by contextual moderators, primarily entity type (government vs. private sector) and organizational maturity. The study’s primary contribution is the development of an integrated, context-contingent conceptual model. By synthesizing the D&M IS Success Model with Agency Theory and the Resource-Based View, this model reframes prior contradictions not as anomalies, but as predictable outcomes of complex contextual interactions. This provides a more cohesive theoretical foundation for future AIS research and offers a nuanced diagnostic tool for practitioners in emerging economies.